Pengembangan Sistem Informasi Asosiasi Jasa Konstruksi dengan Menerapkan Tanda Tangan Digital - Taufan Abdurrachman; Bernard Renaldy Suteja (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Currently, Indonesian government is changing the government system into an Sistem Pemerintahan Berbasis Elektronik (SPBE) or often heard as e-government. With this change in the government system, it has an impact on various sector of life. One of many sectors is construction service sector. LPJK as a non-structural institution under Ministry of Public Works and Public Housing issued a letter to the construction services association regarding the development of integrated application with SIKI LPJK. LPJK and OSS institutions has implemented digital signatures on business entity licensing document. Construction service associations has responded to develop of these regulations by creating an association information system application that implements digital signatures. This research was conducted to apply an digital signatures to the validation of the Membership Card using the secure hash algorithm (SHA) and advanced encryption standard (AES) methods generated through the association information system. This application generates an digital signatures which is implemented with QR Code. The existence of this application is expected to be a form of support for the government which is making changes to the government system.